Activated T killer cells induce apoptosis in lung epithelial cells and the release of pro-inflammatory cytokine TNF-α - Shinbori, Toshifumi; Walczak, Henning; Krammer, Peter H. (European journal of immunology, 2004)
Apoptosis is thought to be involved in lung epithelial cell damage in acute respiratory distress syndrome and interstitial pneumonia. Both the role of apoptosis and its underlying molecular mechanisms in human lung tissue remain unclear. To address these issues, we developed an in vitro assay in which a human lung epithelial cell line and a staphylococcal enterotoxin B (SEB)-reactive human CD8+ CTL line were co-cultured in the presence of SEB. SEB-stimulated CD8+ CTL induced apoptosis in the lung epithelial cell line primarily through the perforin/granzyme-mediated pathway. In these cells, apoptosis was initially independent of death receptor pathways. We also tested the effect of IFN-γ on modulation of apoptosis in lung epithelial cells. In IFN-γ-pretreated lung epithelial cells, CD95 (APO-1/Fas) activation as well as TNF-related apoptosis-inducing ligand (TRAIL) receptor and TNFR activation led to apoptosis. Furthermore, we found that the interaction of SEB-stimulated CD8+ CTL with lung epithelial cells induced an increase in TNF-α secretion. These results suggest an important role for bacterial superantigen-reactive CD8+ CTL in induction of lung epithelial cell apoptosis and in modulation of inflammatory processes in lung tissue.